Thermal degradation mechanisms of the cured phenolic triazine thermoset resin (PT30) studied under nitrogen. (February 2023) - Paul, Benjamin; Bailly, Laurence; Bégué, Didier; Lartigau-Dagron, Christine; Hassoune-Rhabbour, Bouchra; Nassiet, Valérie
Highlights: Identification of PT30 resin degradation products by TGA-IR and TGA-MS. Proposal of a degradation mechanism for PT30 resin in a nitrogen atmosphere. Identification of the initiation degradation reaction based on the results of Density Functional Theory (DFT) calculations which highlight the less energetic network bonds. Description of each step in the chain scissions of the PT30 resin. Description of each step in the creation of degradation products. Abstract: The non-isothermal thermal degradation of the cured phenolic triazine thermoset resin (PT30) was considered under nitrogen atmosphere. Thermogravimetric analyses (TGA) showed that the degradation mechanism was decomposed in three main steps occurring at 440°C, 550°C, and 720°C. To understand the chemical reactions that happen, TGA experiments were coupled with the analyses of the gaseous products by Fourier transform infrared detection (TGA/FTIR) and by mass spectrometry (TGA/MS). A degradation mechanism is proposed based on these experimental results and on Density Functional Theory (DFT) calculations. It was found that carbon dioxide is the main degradation product generated by the oxygen-carbon chain scissions. In the second step, triazine rings' rupture led to the formation of cyanide hydrogen and probably cyanic/isocyanic acid. Then, various aromatic compounds are produced from chain scissions and molecules' recombination. Analyses of these degradation products contributed to proposing assumptions of thermal degradation mechanisms of the PT30 resin.